Refined Minimization of Trapezoidal Fuzzy Quadratic Function: A Fuzzy-Parametric Steepest Descent - Shalini K; Tharasi Dilleswar Rao (Fuzzy Information and Engineering)
This article presents a fuzzy parametric steepest descent approach to address the nonlinear fuzzy optimization problem to achieve improved and refined optimal solutions. Specifically, we examine a quadratic function with trapezoidal fuzzy coefficients. We introduce a unique strategy for expressing these trapezoidal fuzzy coefficients in parametric form. By fine-tuning of these parameters within the range [0, 1] for a given fuzzy function, we gain valuable insights into the convergence behavior of the problem. This innovative methodology allows us to control the solutions. To demonstrate the effectiveness of our method, we provided a numerical example for clarity, showing how our approach excels in managing complex fuzzy situations.